THE OUTCOME OF CLOSED REDUCTION AND CAST IMMOBILIZATION OF COLLE'S FRACTURES USING RADIOLOGICAL PARAMETERS IN THE EMERGENCY DEPARTMENT - Raza, Muhammad Shahbaz; Khan, Shaukat Hayat; Ara, Iffat; Ali, Azmat; Mahmood, Khalid; Wani, Rehan (Journal of Ayub Medical College Abbottabad, 2020)
Background: Distal radius fractures account for most of the injuries presenting in trauma centers. Colle's fractures are defined as fractures within 2.5 cm of the wrist with dorsal angulation of the distal fragment. The cornerstone of treatment remains immobilization of the wrist in a cast. The objective of the study was to determine the outcome of closed reduction and plaster cast immobilization of Colle's fractures in adults using Radiological parameters. It was a descriptive case series study, conducted at the Department of Orthopaedics Sheikh Khalifa Bin Zayed Al Nahyan /CMH Muzaffarabad Azad Kashmir from June 2018 to June 2019. Methods: Patients with distal radius fractures fulfilling the criteria of Colle's fractures presenting in the Emergency Department were selected through non-probability consecutive sampling. They were managed as per stated protocols and followed up for 06 months. Results: A total of 106 patients of either gender were included in this study. The average age of patients was 30.36±4.12. Fall on an outstretched hand is the major cause of Colle's fracture. In the older age group, most of the fractures are caused by falls while trauma was responsible for the younger age group. Normal post reduction radial inclination seen in 72% cases; dorsal angulation was normal in 75% while post reduction height was normal in 91% cases. Post reduction radiological parameters were excellent in 49% and good results were seen in 40%. Poor post reduction anatomical results were found in 11% of cases. Overall, Stewart Anatomical score was 84/100 (p<0.01). Conclusion: A large majority of Colle's fractures achieved excellent Radiological results after treatment by closed reduction and cast immobilization. Keywords: Closed reduction; Cast immobilization; Colle's fracture; radiological parameters.